PADDY GROWTH ANALYSIS AND DISEASE PREDICTION USING FUZZY LOGIC CONTROLLER SYSTEM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Agriculture is the primary source of livelihood for about 60% of Indian population. Indianagriculture needs set of solutions for improvisation of both the farmers and the agriculturalland. Agriculture contributes only 16% GDP for the country but it is the largest sector foremployment. Apart from economy, Indian agriculture needs sustainable, efficient, technicaland mainly productive farming. In this project, Paddy is taken as the field to be improvised.Paddy is categorized as 3 different varieties. Using the basic parameters of an agriculturalland has membership function inputs such as temperature, humidity, sunlight and soilmoisture, the respective membership outputs viz., water irrigation, plant growth and plantdiseases are to be found. Membership functions come under the concept of fuzzy logic. Fuzzylogic basically uses membership functions to determine outputs for all calculations. Using IRcameras, plant growth can be easily monitored and analysed. Using this technique, basicnecessities of an agricultural land can be satisfied and is also useful for productive farming.The main concentration of this idea is based on the cultivation of three different varieties ofpaddy.